Resolving criminal acts of sexual abuse committed by children against children using a restorative justice approach in the Kudus police area - Wibowo, Andrias; Hidayatullah, Hidayatullah (Journal of Law Science, 2024)
Currently the Kudus Resort Police is prioritizing preventing the rise of sexual crimes where the perpetrators and victims are children, by providing education to students so that they can use social media wisely. This research is qualitative research. The approach method used in this research is a sociological/non-doctrinal juridical approach. The data from the research comes from primary data and also secondary data which is then analyzed descriptively qualitatively. The results of the research show that: 1) Resolving criminal acts of sexual harassment committed by children against children using a restorative justice approach can be concluded as follows, that sexual harassment is carried out by children against children is a serious problem that requires appropriate treatment. The restorative justice approach offers a different approach in resolving this case, with a focus on victim recovery, building understanding, and responsibility for the perpetrator. So, in order for its implementation to be appropriate and good, it must pay attention to the following matters: Identification and Understanding of Cases, Involvement of Related Parties, Recovering Victims, Fostering Empathy and Responsibility, 2) Obstacles that may be faced in resolving criminal acts of sexual abuse committed by children against children. children with a restorative justice approach include: The need for safety and protection for victims, difficulty reaching an agreement, complexity of the case, lack of cooperation from the perpetrator, limited resources, legal challenges